Rodinný dům - Studený, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Předmětem bakalářské práce je vypracování projektové dokumentace rodinného domu. Objekt je situován do obce Lipůvka. Dům má dvě nadzemní podlaží a plochou střechu.

The goal of bachelor´s thesis is making the plans of family house. The house is situated in the Lipůvka city. There is two floors in the house and there is a flat roof.
Family house
Keywords: rodinný dům; konstrukce pozemních staveb; dvě patra; plochá střecha; family house; building structures; two floors; flat roof